Targeting ion channels in cystic fibrosis - Mall, Marcus A.; Galietta, Luis J.V. (Journal of cystic fibrosis, 2015)
Mutations in the cystic fibrosis transmembrane conductance regulator (CFTR) gene cause a characteristic defect in epithelial ion transport that plays a central role in the pathogenesis of cystic fibrosis (CF). Hence, pharmacological correction of this ion transport defect by targeting of mutant CFTR, or alternative ion channels that may compensate for CFTR dysfunction, has long been considered as an attractive approach to a causal therapy of this life-limiting disease. The recent introduction of the CFTR potentiator ivacaftor into the therapy of a subgroup of patients with specific CFTR mutations was a major milestone and enormous stimulus for seeking effective ion transport modulators for all patients with CF. In this review, we discuss recent breakthroughs and setbacks with CFTR modulators designed to rescue mutant CFTR including the common mutation F508del. Further, we examine the alternative chloride channels TMEM16A and SLC26A9, as well as the epithelial sodium channel ENaC as alternative targets in CF lung disease, which remains the major cause of morbidity and mortality in patients with CF. Finally, we will focus on the hurdles that still need to be overcome to make effective ion transport modulation therapies available for all patients with CF irrespective of their CFTR genotype.